Evaluation of Signalized Intersection Performance Using SIDRA and MKJI 1997 - Tessar Rizky Permana Nasution (Ridwan Institute, 2022)
Jl. Brigjen Katamso - Jl. Ir. H. Juanda 4-way Intersection is one of the signalized intersections in Medan. The performance of this intersection decreases along with the increasingly viscous flow of vehicles passing at the intersection. The Level of Service at the intersection is in the F category because the mean intersection delay is more than 60 seconds. To determine the solution to the existing traffic problems, efforts are needed to understand the current traffic system. This study uses a simulation model with SIDRA Intersection Version 8 software to calculate the delays and the Level of Services compared with the 1997 MKJI method calculation data. Based on the 1997 MKJI method, the mean intersection delay is 78.67 seconds with the Level of Services is LOS E. Based on the SIDRA Intersection simulation results, the mean intersection delay is 104.6 seconds with the Level of Services = LOS F. From the calculation results using the MKJI 1997 and SIDRA Intersection, there are differences in the value of the mean delay